Fluoxetine prevents acetylcholine‐induced excitotoxicity blocking human endplate acetylcholine receptor. Issue 1 (15th July 2013) - Deflorio, Cristina; Catalano, Myriam; Fucile, Sergio; Limatola, Cristina; Grassi, Francesca
ABSTRACT Introduction: Fluoxetine is an open channel blocker of fetal muscle acetylcholine (ACh) receptor (AChR) and slow‐channel mutant AChRs. It is used commonly to treat patients with slow‐channel congenital myasthenic syndromes. Fluoxetine effects on adult wild‐type endplate AChR are less characterized, although muscle AChR isoforms are differentially modulated by some drugs. Methods: Excitotoxicity assays and patch clamp recordings were performed in human embryonic kidney 293 (HEK) cells expressing wild‐type or slow‐channel mutant human AChRs. Results: Fluoxetine (2–10 μM) abolished ACh‐induced death and decreased ACh‐activated whole‐cell currents in cells expressing all AChR types. In outside‐out patches, fluoxetine rapidly curtailed ACh evoked unitary activity and macroscopic currents. The effect was increased if fluoxetine was applied before ACh. Conclusions: Fluoxetine is an open channel blocker, but it also affects AChR in the closed state. AChR blockade likely underlies the rescue of HEK cells from ACh‐induced death. Muscle Nerve49: 90–97, 2014